Investigation of the Views of 4th Grade Pre-service Mathematics Teachers on the Characteristics of A Good Mathematics Teachers - Kükey, Ebru; Tutak, Tayfun (Fırat University, 2019)
In this study, the characteristics of mathematics teacher were investigated according to the 4th grade pre-service mathematics teachers. As it is aimed to examine the thoughts of pre-service teachers was used a case study of qualitative research methods. The study group consisted of 50 pre-service mathematics teachers 39 female and 11 male. The data obtained through from pre-service teacher with structured interviews were analyzed by content analysis. Themes and the sub-dimensions of themes were determined with analyzing the data. In this context, attitudes towards the course, personal characteristics, field knowledge and professional knowledge themes were obtained. As a result considering the characteristics of the themes, it was determined that the lesson and mathematics loving features came to the forefront under the theme of attitude towards the lesson. In the theme of personal characteristics; self-loving, self-development, being like the profession, understanding the students and have been found to be friendly features. It has been determined that features of associating with the daily life and being expert in the field come to the forefront in the field information theme. In the subject of professional knowledge, it is concluded that students have characteristics such as taking into consideration the readiness levels, using materials, eliminating the negative prejudice, a dominate the class, embodying the abstract concepts, making the lesson fun and associating with other lessons. Considering of these characteristics done training will be very useful in ensuring that students learn more effectively.

Bu çalışmada, matematik öğretmeninin özellikleri 4. sınıf matematik öğretmen adaylarına göre araştırılmıştır. Öğretmen adaylarının bilgilerinin ayrıntılı incelenmesi amaçlandığından araştırmada nitel araştırma yöntemlerinden durum çalışması kullanılmıştır. Çalışma grubunu, 39’u kadın, 11’i erkek olmak üzere toplam 50, 4. sınıf matematik öğretmen adayı oluşturmaktadır. Öğretmen adaylarıyla yapılandırılmış görüşmeler aracılığıyla elde edilen veriler, içerik analizi ile analiz edilmiştir. Verilerin analiz edilmesiyle temalar ve temaların alt boyutları belirlenmiştir. Bu doğrultuda derse yönelik tutum, kişisel özellikler, alan bilgisi ve meslek bilgisi temaları elde edilmiştir. Temaların özellikleri dikkate alındığında derse yönelik tutum teması altında dersi ve matematiği sevdirme özelliklerinin ön plana çıktığı belirlenmiştir. Kişisel özellikler temasında kendini sevdirme, kendini geliştirme, arkadaş gibi olma, mesleğini sevme, öğrencileri anlama ve güler yüzlü olma gibi özelliklerin olduğu sonucuna ulaşılmıştır. Alan bilgisi temasına yönelik olarak günlük yaşamla ilişki kurma ve alanında uzman olma özelliklerinin ön plana çıktığı tespit edilmiştir. Meslek bilgisi temasında ise öğrencilerin hazır bulunuşluk düzeylerini dikkate alma, materyal kullanma, olumsuz ön yargıyı kaldırma, sınıfa hâkim olma, soyut kavramları somutlaştırabilme, derse hazırlık yaparak gelme, dersi eğlenceli hale getirme, diğer derslerle ilişkilendirme gibi özelliklerinin olduğu sonucuna ulaşılmıştır. Bu özellikleri dikkate alarak yapılan eğitim öğretimin, öğrencilerin daha etkili öğrenmelerini sağlamada oldukça faydalı olacağı düşünülmektedir.
4. Sınıf Matematik Öğretmen Adaylarının, İyi Bir Matematik Öğretmeninin Özelliklerine Yönelik Görüşlerinin İncelenmesi